Acute effect of dynamic stretching on endurance running performance in well-trained male runners - Yamaguchi, T.; Takizawa, K.; Shibata, K. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to clarify the acute effect of dynamic stretching (DS) on relative high-intensity endurance running performance. The endurance running performances of 7 well-trained middle- or long-distance male runners were assessed on a treadmill after 2 types of pretreatment. The pretreatments were nonstretching (NS) and DS treatment. In the DS treatment, DS was performed as 1 set of 10 repetitions as quickly as possible for the 5 muscle groups in lower extremities. The endurance running performances were evaluated by time to exhaustion (TTE) and total running distance (TRD) during running at a velocity equivalent to 90% maximal oxygen uptake (VO2max) in each subject. The oxygen uptake (VO2) during running was measured as an index of running economy (RE). The TTE (928.6 ± 215.0 seconds) after DS treatment was significantly (p < 0.01) more prolonged compared with that (785.3 ± 206.2 seconds) after NS. The TRD (4,301.2 ± 893.8 m) after DS treatment was also significantly (p < 0.01) longer than that (3,616.9 ± 783.3 m) after NS. The changes in the VO2 during running, however, did not significantly (p > 0.05) differ between the pretreatments. The results demonstrated that the DS treatment improved the endurance performance of running at a velocity equivalent to 90% VO2max in well-trained male runners, although it did not change the RE. This running velocity is equivalent to that for a 3,000- or 5,000-m race. Our finding suggests that performing DS during warm-up before a race is effective for improving performance.